How to deal with big data? Techno-economic analysis of different storage, processing and analysis alternatives - Marlies Van der Wee; Samaneh Bahreini; Sofie Verbrugge (International Telecommunications Society (ITS), 2016)
It is beyond doubt that the exponential growth in available data will serve many purposes and will be provided for and to many users. To meet the wide range of needs, a business handling data system must meet different criteria. This paper provides an a both qualitative and quantitative assessment of five different data handling systems: a data warehouse, a database, a data portal, a data lake and a single point of contact. The qualitative assessment relies on the PEST framework to determine the strengths and weaknesses of each option, while the quantitative assessment uses the Equipment Cost Modeling Notation (ECMN) to give a high-level estimation of the implementation cost. The paper concludes that there is a clear trade-off between adding functionality and adding cost, and that the most important decision parameters are the need for storage capacity, the need for a standardized structure and data format, the need for integrated analytics and the requested degree of scalability.
Keywords: 330; big data; techno-economic analysis; data storage; data management; data processing